"I have surly passed a limit, it is simply too much": women's and men's experiences of stress and wellbeing when living within a process of housework resignation. (December 2016) - Harryson, Lisa; Aléx, Lena; Hammarström, Anne
Abstract Background Gender inequality within paid and unpaid work exposes women and men to different environments and responsibilities. These gender patterns shape living conditions for women and men, either negatively or positively, by affecting the prospect of good health. Most public health studies of gender and housework are quantitative, and knowledge about the relationship between housework experiences and health for women and men is limited. The aim of this study was to explore the housework experiences and practices of women and men and their experiences of stress and perceived wellbeing from a gender perspective. Methods We conducted thematic interviews with four women and four men living in Sweden, and performed an analysis using the Grounded Theory method. Findings We found that stereotypical gender practices in housework influenced experiences of stress and perceived wellbeing among women and men. Despite proposing gender equality in housework as a means of improving wellbeing, inequality was amplified by the way women and men handle the gendered division of housework. We call this recurring theme "The process of housework resignation", which also constitute the core category in our analysis. "The process of housework resignation" was theorised from the categories "Gender practices in housework", "Experiencing stress and wellbeing" and "Managing daily life". Conclusions Stereotypical gender practices in housework can increase experiences of stress among women and men. Challenging stereotypical masculinities can be a key for breaking the process of resignation in housework and for facilitating improved health among both women and men in heterosexual couple relationships within a Swedish context.